Application of the relativistic random-phase and distorted wave impulse approximations to quasielastic proton-nucleus scattering - Van Niekerk, David Douglas (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Physics))--University of Stelllenbosch, 2010.